KEARIFAN LOKAL BATAK TOBA DALIHAN NA TOLU DAN GOOD GOVERNANCE DALAM BIROKRASI PUBLIK - Armaidy Armawi (Jurnal Filsafat "WISDOM", 2008)
AbstractStarting with the problem of dalihan na tolu as a cultural value and public bureaucracy that based on good governance principles, in the context of local wisdom surely it will be aproblem for Batak Toba community. Local wisdom is not able tosolve directly local problems in their plurality and complexity as it takes place in Batak Toba community. Local wisdom, therefore, in the context of culture is only able to support its community. If it faces other cultures, then, there will be some cultural distortions. In order to eliminate the cultural friction and support community structure, therefore, it needs a more sublime local wisdom to create a creative and intelligence local culture. Someone may critically and ironically ask questions: why, in global era when the world had been a global village, men as a person or a group want to comeback to local images; and what it is like a cultural differential phenomenon that makes priority to the images and just want to be a different performance in the context of deconstruction.Keywords: Dalihan na tolu, Local wisdom, Public buereucrasy